A new species of subgenus Homoneura from Northern China, with information of 12 species newly recorded (Diptera: Lauxaniidae: Homoneura) - Shen, Rongrong; Shi, Li; Li, Wenliang; Wang, Junchao (Zootaxa, 2018)
Homoneura (Homoneura) hanmaensis sp. nov. is described as new to science and 12 species are recorded from China for the first time: Homoneura (Homoneura) albomarginata Czerny, 1932, Homoneura (H.) biumbrata (Loew, 1847), Homoneura (H.) cerina Shatalkin, 2000, Homoneura (H.) euaresta (Coquillett, 1898), Homoneura (H.) filiola Czerny, 1932, Homoneura (H.) kaszabi Shewell, 1971, Homoneura (H.) lamellata (Becker, 1895), Homoneura (H.) mediospinosa Merz, 2003, Homoneura (H.) patella Shewell, 1971, Homoneura (H.) shewelliana Papp, 1978, Homoneura (H.) spinicauda Sasakawa and Ikeuchi, 1982, Homoneura (H.) tenera (Loew, 1846). A few of photographs and illustrations are provided for eight species. Keys are provided to separate eight species groups and Chinese species of eight species groups of subgenus Homoneura.